2019
DOI: 10.1103/physrevb.99.195108
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of rare states and thermalization in a theory with confinement

Abstract: There is a dichotomy in the nonequilibrium dynamics of quantum many body systems. In the presence of integrability, expectation values of local operators equilibrate to values described by a generalized Gibbs ensemble, which retains extensive memory about the initial state of the system. On the other hand, in generic systems such expectation values relax to stationary values described by the thermal ensemble, fixed solely by the energy of the state. At the heart of understanding this dichotomy is the eigenstat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 144 publications
4
96
0
Order By: Relevance
“…This movitates us to study thermalization in our long-range model. Previous studies of the short-range Ising model have observed rapid (strong) or slow (weak) thermalization of one-point functions for different initial states [41,42,48,49,[73][74][75][76]. As first shown in Ref.…”
mentioning
confidence: 62%
“…This movitates us to study thermalization in our long-range model. Previous studies of the short-range Ising model have observed rapid (strong) or slow (weak) thermalization of one-point functions for different initial states [41,42,48,49,[73][74][75][76]. As first shown in Ref.…”
mentioning
confidence: 62%
“…Since there is no classical counterpart of the Holstein polaron model, we refer to the model as being quantum chaotic if its spectral statistics matches those of the GOE. Note that the level-spacing statistics (to be studied below) can not distinguish between a completely ergodic system and a system with a nonzero number of nonergodic eigenstates whose fraction vanishes in the thermodynamic limit [82][83][84][85][86][87][88][89]. In Sec.…”
Section: Quantum-chaos Indicatorsmentioning
confidence: 99%
“…In a related development, it was proposed that atypical eigenstates of one Hamiltonian can be "embedded" into the spectrum of another, ETH-violating, Hamiltonian [33]. However, although the collection of models that feature atypical eigenstates is rapidly expanding [34][35][36][37][38], including recent examples of topological phases [39] and fractons [40], their relation to periodic dynamics remains largely unclear.In this paper we systematically construct interacting lattice models that exhibit periodic quantum revivals when quenched from a particular product state. The basic building block has a Hilbert space containing N c states ("colors") and a time-independent Hamiltonian that yields periodic unitary dynamics, U(t + T ) = U(t).…”
mentioning
confidence: 99%
“…In a related development, it was proposed that atypical eigenstates of one Hamiltonian can be "embedded" into the spectrum of another, ETH-violating, Hamiltonian [33]. However, although the collection of models that feature atypical eigenstates is rapidly expanding [34][35][36][37][38], including recent examples of topological phases [39] and fractons [40], their relation to periodic dynamics remains largely unclear.…”
mentioning
confidence: 99%